How metabolic syndrome patients cope with stress: A qualitative study - Nor Fadhilah, Abdullah; Radziah, Mohd Fauzi; Sakinah, Harith (2015)
Background: Having multiple kinds of health problems among metabolic syndrome patients may cause them stress. Life events also may worsen their stress. Negative stress affects not only their physical but also emotional health. Various coping styles are used in order to deal with their stress. However, not all coping styles can overcome their stress. Objectives: This study aims to explore the coping styles that have been employed by the stressed metabolic syndrome patients in Hospital Universiti Sains Malaysia, Malaysia. Method: Semi-structured interviews were conducted with the stressed metabolic syndrome patients in Hospital Universiti Sains Malaysia. A purposive sampling was selected among stressed respondents, as fifteen of them participated in this study after saturation data was reached. The qualitative data was analysed using content analysis and was categorized into dysfunctional, problem-focused and emotion-focused coping. Results: The themes that emerged were; self-distraction, venting, behavioural disengagement, denial and self-blame. These were categorized as dysfunctional coping; acceptance, religion and emotional support as emotion-focused coping and active coping and instrumental support which were categorized as problem-focused coping. Other new coping styles identified were physical intervention, avoidance and emotion suppression. Conclusion: Coping styles has direct influence on the feeling of stress. Stressed patients used many dysfunctional coping styles rather than other categories of coping which lead them to remain in stress. These data highlighted the need to educate patients about good coping styles to give them additional skills in managing their stress thus improving their health.